Robot‐Assisted Gait Training in a Patient With Hereditary Spastic Paraplegia. Issue 2 (22nd September 2014) - Seo, Han Gil; Oh, Byung‐Mo; Kim, Keewon
Abstract: Robot‐assisted gait training has been investigated for restoring walking through activity‐dependent neuroplasticity in persons with various neurologic disorders. This case report presents the outcome of robot‐assisted gait training combined with physiotherapy in a 28‐year‐old man with pure hereditary spastic paraplegia. The patient participated in 25 training sessions over 6 weeks. Improvements were noted in his walking speed and balance after the training, but gait kinematics and kinetics showed no remarkable changes before and after the training. Robot‐assisted gait training may be useful for providing intensive gait training in patients with hereditary spastic paraplegia because the patient's walking speed and balance improved after the training.